2015
DOI: 10.1038/nature14444
|View full text |Cite|
|
Sign up to set email alerts
|

Wild-type microglia do not reverse pathology in mouse models of Rett syndrome

Abstract: Rett syndrome (RTT) is a severe neurodevelopmental disorder caused by mutations in the X chromosomal gene Methyl-CpG-binding Protein 2 (MECP2) (1). RTT treatment so far is symptomatic. Mecp2 disruption in mice phenocopies major features of the syndrome (2) that can be reversed upon re-expression of Mecp2 (3. It has recently been reported that transplantation of wild type (WT) bone marrow (BMT) into lethally irradiated Mecp2tm1.1Jae/y mice prevented neurologic decline and early death by restoring microglial pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
92
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(99 citation statements)
references
References 12 publications
6
92
1
Order By: Relevance
“…Interestingly, it has been shown that phagocytic activity of the WT bone marrow-derived cells is necessary to rescue the Rett syndrome phenotype. In contrast, other studies investigating the function of microglia in the development of Mecp2 deficiency-induced Rett syndrome revealed enhanced phagocytosis of dendritic spines during synaptic pruning that is not rescued by reintroduction of Mecp2 into microglia (77,78). These studies suggest a contribution of microglia in disease pathology, but other mechanisms of disease could also be involved.…”
Section: Physiological Function Of Microglia In the Adult Braincontrasting
confidence: 44%
“…Interestingly, it has been shown that phagocytic activity of the WT bone marrow-derived cells is necessary to rescue the Rett syndrome phenotype. In contrast, other studies investigating the function of microglia in the development of Mecp2 deficiency-induced Rett syndrome revealed enhanced phagocytosis of dendritic spines during synaptic pruning that is not rescued by reintroduction of Mecp2 into microglia (77,78). These studies suggest a contribution of microglia in disease pathology, but other mechanisms of disease could also be involved.…”
Section: Physiological Function Of Microglia In the Adult Braincontrasting
confidence: 44%
“…We previously described a transgenic mouse model for monitoring MeCP2 expression with a fusion of the MeCP2 gene with firefly luciferase and hygromycin resistance genes (MeCP2-FL-HR) (12). Whereas the fusion protein proved unstable, resulting in a MeCP2 loss-of-function phenotype in mice, the reporter expression pattern paralleled the expression of the native MeCP2 gene (12).…”
Section: Resultsmentioning
confidence: 99%
“…Whereas the fusion protein proved unstable, resulting in a MeCP2 loss-of-function phenotype in mice, the reporter expression pattern paralleled the expression of the native MeCP2 gene (12). To develop clonal cell lines that have the transgene on either the active (Xa) or inactive X chromosome, we immortalized tail tendon fibroblasts from heterozygous MeCP2-FL-HR/MeCP2 female mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have suggested that non-neuronal CNS cells such as astrocytes and microglia play a crucial role in the RTT phenotype and that repair of these cells alone provides robust phenotype amelioration [111,139,140]. While HR levels in these dividing cells will be higher than in neurons it will not be enough to compensate for the vastly greater number of cells that will be repaired imprecisely by NHEJ.…”
Section: Other Gene-targeted Strategies In Rttmentioning
confidence: 99%